ATHROPOMETRY STUDY: FACTOR AFFECTING CEPHALIC INDEX OF THE TIMORESE TRIBE IN KUPANG CITY-NTT - regina m hutasoit (Cendana Medical Journal, 2026)
The anthropometric size of a person's head will give a person a distinctive appearance and then form the characteristics of a particular tribe or race. The cephalic index is influenced by several factors such as gender, age, ethnicity, race, geographical environment and genetics. Factors affecting the anthropometric size of the head such as gender and age which are considered as general identities were observed and analyzed to determine the factors influencing the size of the cephalic index so that Timorese tribe identity can be observed and developments that occur can be observed in the future. In addition, it completes the primary data for identification from Timor ethnicity. Method: Observational analytic research with a cross sectional design on 100 respondents with the identity of the Timorese ethnic group aged 11-50 years, male and female. Results: were analyzed with Maan-Whitney, giving results not significant difference in cephalic index mean for sex (p=0,992) and age (p=0.161). Conclusion. both sex and age factors do not have a significant effect on the cephalic index when applied to individuals who come from ethnic groups, geographic environment and age that are not much different. Based on gender, the head shape of the Timorese is still dominated by the brachicephalic shape